Evidence for Widespread Convergent Evolution around Human Microsatellites - Vowles, Edward J; Amos, William (PLOS Biology, 2004)
An analysis of sequences flanking microsatellites in the human and chimpanzee genomes suggests that mutations do not occur independently and randomly, as is commonly assumed in models of DNA sequence evolution.